Analisis Pembangkit Listrik Hibrid Untuk Kawasan Universitas Teuku Umar Meulaboh - Sulaiman Ali; Maidi Saputra (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2015)
Which more lower deficit of fossil energy for generated power plant, in order to need to do wind power generation plant analysis based on renewable energy which is wind turbine horizontal type. This study is analyzing a power system with electric power load for Teuku Umar University by using a hybrid power generation system which HOMER between wind turbines and diesel generators. Wind resources are used is measured by BMKG Meulaboh Station, which is 6 m/s. The results of the simulation is given by the value of the Net Present Cost (NPC) and the lowest, in the amount of $43,686,940, Cost of Energy (COE) is 16.993 $/kWh for the value of Renewable Factor (RF) was 40% and for the value of Renewable Factor (RF), the largest at 58%, the value of the Net Present Cost (NPC) amounted to $ 68,091,256 and Cost of Energy (COE) is 16.993 $/kWh. Keywords: Wind Turbine, Homer, Power Plants, Net Present Cost (NPC), Renewable Factor (RF)